Frontiere oltre confine: fronti e interstizi della gestione migratoria nello spazio EurAfricano - Paolo Gaibazzi (Archivio Antropologico Mediterraneo)
The article adapts two classic notions of frontier in order to analyse the delocalisation of migration control and management in the Euro-African space. It deals specifically with the so-called externalisation of European borders to Africa, building on ethnographic research in The Gambia on assisted repatriation and reintegration from transit countries along the Mediterranean routes. On the one hand, the article proposes to read externalisation as a front of control advancing on the African continent, albeit not in a linear and irreversible fashion, and partly reproducing past frontier dynamics. On the other, an interstitial frontier perspective inspired by Igor Kopytoff is shown to be useful to avoid Eurocentric and state-centric biases, and to analyse externalisation as an emergent political order at the intersection between different regimes of mobility in in/formal or opaque institutional spaces.